Who arrives first: EMS, fire-fighter or lay responder? The rally to the suspected out-of-hospital cardiac arrest. (14th October 2021) - Berglund, E; Ringh, M; Claesson, A; Svensson, L; Jonsson, M
Abstract: Background: Time is the crucial factor for "the chain of survival" in Out-of-Hospital Cardiac Arrest (OHCA). We aimed to compare different response time intervals for dispatched lay responders, fire fighters and emergency medical services (EMS). Methods: Mobile phone dispatched lay responders in two large Swedish regions (4 million inhabitants) were positioned and timed from alert until arrival to the place of the suspected OHCA. For each suspected OHCA the first arriving lay responder was compared to the first arriving EMS and first fire fighter unit. Time intervals, from witness call-to-dispatch and dispatch-to-arrival was measured. Results: During 22 months a total of 2631 suspected OHCAs were included. The median time from call-to-dispatch was 1.8 (95% CI: 1.7–1.8) for EMS, 2.9 (95% CI: 2.8–3.0) for fire-fighter units and 3.0 (95% CI: 2.9–3.1) for lay responders. The median time from dispatch-to-arrival was 8.3 (95% CI: 8.1–8.5) for EMS, 6.8 (95% CI: 6.7–6.9) for fire fighters and 6.0 (95% CI: 5.7–6.2) for lay-responders who tried to fetch an AED and 4.6 (95% CI: 4.5–4.8) minutes for lay-responders who ran to perform bystander CPR. Conclusion: First arriving lay responder have the shortest dispatch-to-arrival time when compared to both fire fighters and EMS. However, this advantage is diminished by a one-minute delay compared to EMS until they are alerted. New solutions are needed for the fully use of mobile dispatched lay responders. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020, For the ESCAPE-NET investigators